List of All Base-edge Formulas

All Base-edge Formulas List

Base Edge of a Pyramid

Formula:

b=√ (3 x (v / h))


Where,

b = base length
v = volume of square pyramid
h = height of square pyramid

Related Calculator:

Base Edge of a Right Rectangular Pyramid

Formula:

l = (3 x v) / (h x w)


Where,

l = Base Length of Pyramid
v = Volume of Pyramid
h = Height of Pyramid
w = Base Width of the Pyramid

Related Calculator:


Base Edge of a Pentagonal Pyramid

Formula:

b = (6 x v) / (5 x h x a)


Where,

b = Base Length
v = Volume of the Pyramid
h = Height of the Pyramid
a = Apothem Length of Pyramid

Related Calculator:

Base Edge of a Triangular Pyramid

Formula:

Base Edge = (6 x Volume) / (Apothem Length x Height)

Related Calculator:


english Calculators and Converters

Ask a Question


Sitemap